Multi-criteria path rationalization in the conditions of multi-type passenger transport systems - V. V. Egorov (Вестник университета, 2021)
The article proposes methods of searching passenger travel routes in conditions where one or more optimization criteria must be taken into account in the presence of a pedestrian system and multi-type transport systems with their topologies, sets of parameters and tariff plans. The author carried out the research by means of mathematical modeling of the transport system in the form of its deterministic graph model. The author chose Dijk-stra's algorithm as the basic algorithm, on the basis of which the modifications of the previous ones were carried out and the construction of a new search technique was carried out. As a result, the study obtained algorithms for solving single-criteria and multi-criteria problems on graphs. For multicriterial problems, the author used the convolution method and the method of ordering criteria by the degree of decreasing their significance. The field of application of the developed algorithms is information systems focused on the end user and on the structures that design and manage transport networks.